Okoljevarstvena psihologija kot raziskovalno področje - Kalc, Polona (Psihološka obzorja (Ljubljana), 2015)
During the past decades the importance of psychology has become more prominent when addressing environmental issues. At the turn of the millennium a new field of psychological research was introduced to scientific community. The so-called conservation psychology strives to merge and spur basic and applied psychological research from the field of (pro)environmental behaviour and sustainable development. Together with environmental and population psychology, it forms Division 34 of American Psychological Association. However, conservation psychology is not a broadly known and renowned field of study in Slovenia. Therefore, the main purpose of the present article is to introduce conservation psychology as a possible field of study to Slovenian psychologists.
Keywords: conservation psychology; psihologija; psychology; environmental psychology; okoljska psihologija; varstvo okolja; environmentalism; environmental protection; sustainable development; trajnostni razvoj